Reforms and Innovations in the German Public Prosecution System: A Contemporary Overview - Muhammad Ahmed Saeed , Dr. Muhammad Bilal (Corresponding Author) (Migration Letters, 2024)
Germany boasts one of the world’s most exemplary public prosecution systems. As a modern democratic country that respects human rights and the principles of natural justice, Germany operates under a Civil Law framework with an inquisitorial system for criminal justice. The judiciary is fully independent and has the power of judicial review to examine decisions by the executive and legislature. The German constitution ensures the separation of powers among the judiciary, legislature, and executive, and protects human rights and natural justice principles. Historically, German courts held investigative powers, but these responsibilities now lie with the Independent Public Prosecution Office. This office objectively investigates cases, gathering both inculpatory an[1]d exculpatory evidence, and considers all relevant circumstances affecting the trial’s outcome. It is empowered to handle minor offenses (Vergehen) and can dispose of cases before they reach court, thereby reducing the courts’ workload. The Public Prosecution Office is obliged to investigate all applications for criminal proceedings. It conducts preliminary investigations, which may involve explicit methods like interviews and interrogations, as well as implicit methods such as surveillance and wiretapping. After collecting all evidence, the office decides whether to drop the case or indict the accused. As the guardian of the rights of accused persons, witnesses, and victims, the Public Prosecution Office ensures no evidence is gathered by infringing on the accused’s rights. If evidence is collected improperly, the prosecutor can discard it. The office also ensures the accused’s right to a fair trial before an impartial judge. During investigation and trial, an accused person in Germany may have three different statuses: suspect, accused, and defendant. A person is initially a "suspect" if believed to be culpable. They become an "accused" when the prosecution decides to indict them. If the court decides to proceed with the case, the accused then becomes a "defendant."